2018
DOI: 10.14740/jocmr3320w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Difficult Intubation in Emergency Department by Intubation Assessment Score

Abstract: BackgroundThe difficult intubation is associated with failure of emergency tracheal intubation. This study aimed to develop and validate a model for predicting difficult intubation in emergency department (ED).MethodsA cross-sectional study was conducted in the ED. We collected data from all consecutive adult patients who underwent emergency tracheal intubation. Patients were excluded if they were intubated by low experience intubator. The difficult intubation was defined by grade III or IV of Cormack and Leha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…There were 218 test comparisons from 92 studies for difficult laryngoscopy, 72 comparisons from 50 studies for difficult intubation, 18 comparisons from seven studies for difficult facemask ventilation and two comparisons from two studies for failed intubation. Overall, the median (IQR [range]) number of participants per study, proportion of female participants, age and body mass index were 380 (200–662 [14–103,728]), 53% (44–64% [0–100%]), 45 (39–52 ) years and 27.3 (24.8–30.0 ) kg.m −2 , respectively. All studies except four performed airway management in operating theatres, two in the pre‐hospital setting and the others occurred in emergency rooms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 218 test comparisons from 92 studies for difficult laryngoscopy, 72 comparisons from 50 studies for difficult intubation, 18 comparisons from seven studies for difficult facemask ventilation and two comparisons from two studies for failed intubation. Overall, the median (IQR [range]) number of participants per study, proportion of female participants, age and body mass index were 380 (200–662 [14–103,728]), 53% (44–64% [0–100%]), 45 (39–52 ) years and 27.3 (24.8–30.0 ) kg.m −2 , respectively. All studies except four performed airway management in operating theatres, two in the pre‐hospital setting and the others occurred in emergency rooms.…”
Section: Resultsmentioning
confidence: 99%
“…We identified further studies from references of retrieved articles and used citation tracking in Science Citation Index. The search was updated in March 2018 but we have not incorporated the results from 27 studies in this review.…”
Section: Methodsmentioning
confidence: 99%
“…The training level of operator should be considered, so similar study excluded the case which is intubated by low experience operators, including last year of medical student and rst-year internist in general practice (45). Therefore, we only included the patients who were intubated by chief residents and attending physicians, and the GAP analysis also demonstrated that the variable of operator has almost zero correlation to all of the adverse index such as intubation injury, number of attempts, and even di cult intubation, implied that our chief residents and attending physicians have almost equal level of the skill of endotracheal intubation, so there was less experience related bias in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have proposed combinations of these measures for precise prediction. Srivilaithona et al showed that the weighted combination of ve independent predictors (male sex, large tongue, limited mouth opening, poor neck mobility, and obstructed airway) helped to discriminate di cult intubation patients (7); however, the use of so many predictors is not suitable for ED. In this study, we evaluated the incidence and predictive factors of di cult intubation and developed an easy-to-use predictive formula for emergency physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of difficult intubation in the ED varies from 2% to 26%, owing to different study definitions and populations [10][11][12]. The incidence of our study was 35.5%, higher than previous studies, because we defined difficult intubation as Cormack & Lehane classification grade III or IV in the first intubation attempt rather than the final successful attempt [10,11]. We thought that it should be a fair comparison of different patients, and we supposed participating physicians should be well prepared before the first intubation attempt.…”
Section: Discussionmentioning
confidence: 99%